THE IMPLEMENTATION OF PROJECT-BASED ASSIGNMENT IN ONLINE LEARNING DURING COVID-19 - Aldi Yuliansyah; Mutiara Ayu (Journal of English Language Teaching and Learning, 2021)
By implementation of online systems strategy indirectly forces teachers and students to master the uses of technology in learning process. Online learning is needed to facilitate the teacher delivering the material to students during the pandemic situation.  From this condition, it is suitable for teachers to implement Project Based Learning as it allows students to design, plan and carry out an extended project that produces a publicly exhibited output such as a product, publication or presentations Project Based Learning improves the students’ media research skills provides a real-world connection to context. The students conduct research using multiple information resources. By locating the resources themselves, their research skills develop and improve. Project Based Learning increases the students‟ collaboration. In the processing stages, students create and organize their own groups. They share knowledge and collaboratively construct their products. Through collaboration, they develop social communication skills and obtain multiple perspectives.